The Influence of Religious Maturity Level on Bullying Behavior Among Senior High School Students - Zannah, Hikmah Aulia; Rahmat, Munawar; Anwar, Saepul (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study aims to determine the extent of the relationship between the level of religious maturity and bullying behavior among high school students. Religious maturity is seen as an important indicator in shaping student behavior, especially in suppressing the tendency to commit aggressive acts, whether physically, verbally, psychologically, socially, or through digital media. The approach used in this study is a quantitative approach with a correlational design. The research data were collected using a Likert scale questionnaire, 1–4, containing indicators of religious maturity and various forms of bullying behavior. The research sample was 115 grade XI students at SMAN 4 Sukabumi City who were selected proportionally through stratified random sampling techniques from a total population of 161 students. Data analysis was carried out by validity and reliability tests, classical assumption tests, and hypothesis testing using simple linear regression analysis. The results of the analysis showed that there was a significant influence of the level of religious maturity and bullying behavior. The regression model obtained showed that religious maturity contributed 64% to the bullying behavior variable. This finding strengthens the assumption that the higher the level of religious maturity of students, the lower their tendency to engage in bullying behavior. This study recommends strengthening religious education that emphasizes understanding and experiencing spiritual values as a preventive strategy against deviant behavior in the school environment.